A Pipeline for Monitoring and Maintaining a Text Classification Tool in Production - Ohata, Elene F.; Mattos, César Lincoln C.; Rêgo, Paulo Antonio L. (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2024: Anais do LI Seminário Integrado de Software e Hardware, 2024)
Text classification has been a core component of several applications. Modern machine learning operations strategies address challenges in deploying and maintaining models in production environments. In this work, we describe and experiment with a pipeline for monitoring and updating a text classification tool deployed in a major information technology company. The proposed fully automatic approach also enables visual inspection of its operations via dashboards. The solution is thoroughly evaluated in two experimental scenarios: a static one, focusing on the Natural Language Processing (NLP) and Machine Learning (ML) stages to build the text classifier; and a dynamic one, where the pipeline enables automatic model updates. The obtained results are promising and indicate the validity of the implemented methodology.